The Positive Role of Self-Concept and Religiosity in Reducing the Sense of Alienation in College Students - Ningsih, Ike Utia (Psikis : Jurnal Psikologi Islami, 2024)
This study aimed to empirically explore the influence of self-concept and religiosity on the sense of alienation in university students. The population in this study consisted of 125 students with a purposive sampling technique based on the Slovin formula; 95 students were determined as research subjects. The measurement tool used in this study was a scale compiled by the researcher himself. The scales used were a self-concept scale based on aspects proposed by Hurlock, a religiosity scale based on aspects from Fetzer, and a sense of alienation scale referring to aspects raised by Hurlock. The data analysis method used was multiple regression. The results of the hypothesis analysis showed that the correlation coefficient was 0.745 with p = 0.000 where (p < 0.01), meaning that there was a positive and significant influence between self-concept and religiosity in reducing the feeling of alienation in college students.